DEFINITION OF TEACHER'S RATING IN VIEW OF HIS PUBLICATION ACTIVITY - Oleg V. Mikhailov (Moscow Polytechnic University, 2016)
The article analyzes separate positions of acting teacher rating (TR) worked out at Kazan National Research Technological University (KNRTU), in 2014. It has been shown that the most significant (in numerical terms) contribution to the TR can be made owing to the publication of scientific articles in journals with high impact factor indexed in the Web of Science and (or) Scopus citation database, and, also, due to the innovation process. It was also noted that for almost all teachers of KNRTU having a high (more than 1,000) TR value, a decisive contribution to TR was introduced owing to sufficient scientific activity.